2015
DOI: 10.1038/srep16963
|View full text |Cite
|
Sign up to set email alerts
|

MIG-seq: an effective PCR-based method for genome-wide single-nucleotide polymorphism genotyping using the next-generation sequencing platform

Abstract: Restriction-enzyme (RE)-based next-generation sequencing methods have revolutionized marker-assisted genetic studies; however, the use of REs has limited their widespread adoption, especially in field samples with low-quality DNA and/or small quantities of DNA. Here, we developed a PCR-based procedure to construct reduced representation libraries without RE digestion steps, representing de novo single-nucleotide polymorphism discovery, and its genotyping using next-generation sequencing. Using multiplexed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
348
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 291 publications
(360 citation statements)
references
References 28 publications
(30 reference statements)
0
348
0
Order By: Relevance
“…To obtain genome‐wide SNP information of these species groups from total DNA, we conducted MIG‐seq method (Suyama & Matsuki, ). MIG‐seq is a type of reduced representation sequencing such as restriction site‐associated DNA sequencing, and especially effective for low‐quality DNA and small quantities of DNA (Tamaki, Yoichi, Matsuki, Suyama, & Mizuno, ), which was performed for viviparid snails in previous research (Hirano et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain genome‐wide SNP information of these species groups from total DNA, we conducted MIG‐seq method (Suyama & Matsuki, ). MIG‐seq is a type of reduced representation sequencing such as restriction site‐associated DNA sequencing, and especially effective for low‐quality DNA and small quantities of DNA (Tamaki, Yoichi, Matsuki, Suyama, & Mizuno, ), which was performed for viviparid snails in previous research (Hirano et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…MIG‐seq is a type of reduced representation sequencing such as restriction site‐associated DNA sequencing, and especially effective for low‐quality DNA and small quantities of DNA (Tamaki, Yoichi, Matsuki, Suyama, & Mizuno, ), which was performed for viviparid snails in previous research (Hirano et al, ). Preparation of the MIG‐seq library was executed under a method modified from Suyama and Matsuki () using an Illumina MiSeq Sequencer (Illumina), and an MiSeq Reagent Kit version 3 (150 cycle; Illumina) (Hirano et al, ; Y. Tsunamoto et al, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Some common NGS approaches include whole genome resequencing, reduced‐representation sequencing (RRS), and pooled DNA sequencing (Pool‐seq). RRS methods include genotyping‐by‐sequencing (GBS; Davey et al., 2011), restriction site‐associated DNA sequencing (RADseq; Baird, Etter, Atwood, & Currey, 2008; Peterson, Weber, Kay, Fisher, & Hoekstra, 2012), and multiplexed ISSR genotyping‐by‐sequencing (MIGseq) (Suyama & Matsuki, 2015). By restricting sequencing to a fraction of the genome (e.g., restriction enzyme sites ~1% of the genome), GBS and RADseq can typically generate tens of thousands of polymorphisms for monitoring variation.…”
Section: Toward a Monitoring System For Intraspecific Variationmentioning
confidence: 99%
“…Our rearing experiments indicated that P. urniphila is a gregarious parasitoid because males and females were reared from a single host larva (Table 1). To confirm polyembryonic reproduction by P. urniphila , we need histological survey or MIG-seq analysis (Suyama and Matsuki 2015) that discriminate individuals originated from clonal division and sexual reproduction.…”
Section: Taxonomymentioning
confidence: 99%